“Teachers’ Perspectives on Learning Activity Sheets’ Effectiveness as Reinforcement Tools in Grade 11 Earth and Life Science” (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This qualitative study underscores the importance of Learning Activity Sheets (LAS) as reinforcement tools in Grade 11 Earth and Life Science, particularly in enhancing student comprehension, engagement, and independent learning within senior high school classrooms. Despite the widespread implementation of LAS, a research gap remains in the limited qualitative literature that examines teachers’ perspectives on their instructional effectiveness and the practical challenges encountered during classroom implementation. Addressing this gap, the study aimed to explore how LAS support student learning, identify the challenges teachers face in using them, and describe strategies employed to enhance their effectiveness. A qualitative research design was utilized, employing purposive sampling to select Grade 11 science teachers as participants. Data were collected through semi-structured interviews that allowed teachers to share their experiences and insights, and the responses were analyzed using thematic analysis to identify recurring patterns and meaningful themes. Findings revealed that teachers perceive LAS as effective instructional tools that improve student understanding, engagement, and independent learning, particularly when activities are well-structured, promote collaboration, and are linked to real-life contexts. However, teachers also reported challenges such as limited instructional time, varying levels of student motivation, and difficulties in aligning LAS with lesson objectives. Anchored on B.F. Skinner’s Reinforcement Theory and Piaget’s Constructivist Theory, the study implies that thoughtfully designed and contextually relevant LAS can strengthen instructional practices, promote learner-centered engagement, and improve learning outcomes in Earth and Life Science. The findings provide valuable insights for teachers, curriculum developers, and school administrators in improving the design and implementation of LAS in senior high school science education.